VIDEO PENGAYAAN E- LEARNING POLIBATAM DALAM BENTUK ANIMASI - Hutagalung, Charolinda; Amalia, Yessy Kusumah; Rahmi, Anis; Mu'minin, Amirul (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2023)
The development of technology today has taken many roles from various fields, one of which is in the field of education. At this time many educational institutions use internet technology to facilitate the learning process. The application of internet technology is implemented in the form of an online learning system or based on e-learning. With the development of this technology, it is necessary to have an information media that can make it easier for users to obtain information about how to use each feature in the learning system. One of the information media that is currently widely used is information media in the form of video in the form of animation. Submission of information in the form of animated videos will be more interesting and easy for users to understand. The purpose of this study is to create several 3D animated videos as information media regarding the use of features in the Politeknik Negeri Batam e-learning system. The research uses the method of designing or creating products consisting of several stages, namely pre-production, production, and post-production. The results of the research are in the form of four animated videos that contain the use of features in Politeknik Negeri Batam e-learning, each video lasting between 2-3 minutes. The results of this study are expected to provide information about the use of the learning features of Politeknik Negeri Batam so that the use of e-learning can make it easier for students and lecturers to carry out the learning process.